Three years of football play maintains NordBord eccentric hamstring strength in Division I athletes - Vandenakker, J.; Wilwand, M.; Mortensen, B. B.; Johnson, A. W. (International Journal of Exercise Science Conference Proceedings, 2025)
In American football, the development of strength, power, speed, and conditioning is crucial throughout a season and college career to enhance athletes` performance and prevent injury. Eccentric knee flexor strength is important for optimal athletic performance and injury risk reduction; therefore, assessment of eccentric hamstring strength (EHS) is critical.